2020
DOI: 10.3390/ani10122339
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Milking and Housing Environment on Milk Microbiota

Abstract: The aim of the present study was to determine the effects of farming environments on microbiota in raw milk and to assess the relationship among microbes by 16S rRNA sequencing methods. Samples of raw milk, cow trough water, teat dip cup, teat, teat liner, dairy hall air, cowshed air, feces, feed, and bedding from two farms were collected. The two highest abundant bacterial groups of Moraxellaceae and Staphylococcaceae were found in milk and teat liner samples, respectively, at Zhengzhou farm, Henan Province. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…Metzger et al [ 40 ], reported that there were differences in milk microbiota composition for cows kept on manure solids, recycled sand, sawdust and new sand. It has been demonstrated that the milk microbiota is a dynamic community with the shift of environment [ 11 , 40 , 41 , 43 ]. Nguyen et al [ 44 ], found that differences in milk microbiota derived from two farms at the family level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metzger et al [ 40 ], reported that there were differences in milk microbiota composition for cows kept on manure solids, recycled sand, sawdust and new sand. It has been demonstrated that the milk microbiota is a dynamic community with the shift of environment [ 11 , 40 , 41 , 43 ]. Nguyen et al [ 44 ], found that differences in milk microbiota derived from two farms at the family level.…”
Section: Discussionmentioning
confidence: 99%
“…Manure solids used as bedding have high bacterial counts, leading to dirtier udders and higher coliform and streptococci counts than when sand or organic non-manure materials are used [ 9 ]. The diversity and abundance of the milk microbiota is affected by the environment where cows are housed (including their bedding [ 10 ]), and milked (with milk microbiota being similar to the microbiota on teat liners and teat dip cups [ 11 ]). High bacterial counts in bedding translate to high bacterial counts on cows’ teats, adversely affecting udder health and milk quality [ 5 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A quantity of 200 ml of clean in place (CIP) water from the dairy factory was collected every day, and stored in sterile sampling bottles. For the collection method of air samples, referring to Du et al ( 16 ), milk samples (50 ml) were collected in triplicate each day at each sampling point for 4 consecutive days and immediately stored at −20°C until analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, the Source Tracker modeling based on 16S rDNA sequencing and analysis of microbial contamination sources for raw milk have been widely used. Du et al used Source Tracker modeling based on 16S rDNA sequencing to analyze the sources of microbial contamination in raw milk and found that the teat liner and teat dip cup were the main sources of contamination ( 16 ). Wu et al used Source Tracker modeling based on 16S rDNA sequencing to analyze the source of microbial contamination in farm milk using automatic milking systems and found that airborne dust was the most important source of contamination ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…The temperature of the raw milk after extrusion is rapidly reduced to <6°C and kept at this level during storage and transportation. Interestingly, the presence of psychrotrophic bacteria can result in contamination of the milk even at these storage temperatures ( Ahmed et al, 2014 ; Fusco and Quero, 2014 ; Hahne et al, 2019 ; Du et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%